2006 IEEE International Symposium on Geoscience and Remote Sensing 2006
DOI: 10.1109/igarss.2006.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of JPEG and JPEG2000 Lossy Compression on Remote Sensing Image Classification for Mapping Crops and Forest Areas

Abstract: This study measures the effect of lossy image compression on the digital classification of crops and forest areas. A hybrid classification method using satellite images and other variables has been used. The results contribute interesting new data on the influence of compression on the quality of the produced cartography, both from a "by pixel" perspective and regarding the homogeneity of the obtained polygons. The classified area in classifications only carried out with radiometric variables or with NDVI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…It is important to stress that the goal is not to transmit images that might be visually pleasing, but rather ones that contain enough information to perform the task (Figure 4). Previous studies [16][17][18] have shown mixed effects of compression on image classification. In this study, classification accuracy was shown to improve with increased image down-sampling and/or compression more universally even than in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to stress that the goal is not to transmit images that might be visually pleasing, but rather ones that contain enough information to perform the task (Figure 4). Previous studies [16][17][18] have shown mixed effects of compression on image classification. In this study, classification accuracy was shown to improve with increased image down-sampling and/or compression more universally even than in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Their general conclusion is that if the compressed imaged size is 10% of the original image size there is no influence on image quality or on the quality of the DEM generated. Regarding thematic quality, results obtained in classifications in previous studies where not conclusive 7,8,9,10 but recent ones conclude that a compression ratio of 0.4 can be used in the worse case 11 .…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies have demonstrated that, for the majority of applications, a certain degree of lossy compression might be applied without affecting the results of final applications: digital elevation model generation [13,14], and digital image classification [15][16][17].…”
Section: Introductionmentioning
confidence: 99%